2018
DOI: 10.1007/s10661-018-6701-8
|View full text |Cite
|
Sign up to set email alerts
|

17α-Ethinylestradiol and 17β-estradiol removal from a secondary urban wastewater using an RBC treatment system

Abstract: The presence of micropollutants that include endocrine-disrupting compounds (EDC) in aquatic environments is currently one of the most relevant aspects of water quality due to their adverse effects on aquatic organisms and human health. From the several categories of EDC, 17β-estradiol (E2) is a natural hormone, which is prevalent in vertebrates, associated with the female reproductive system and maintenance of the sexual characters. 17α-Ethinylestradiol (EE2) is a synthetic hormone produced from the natural h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Indeed, some studies have shown that the presence of EDCs in anthropized watercourses, due to inadequate urban wastewater management, can lead to pollution of drinking water sources. Since drinking water treatment technology can be ineffective in removing these compounds, consumption of tap water can cause the consequent EDC intake [18,20,70]. Exposure in urban areas may also occur through inhalation of atmospheric EDCs released by human activities (e.g., traffic, industrial processes, waste incineration) [21,71].…”
Section: Relationship Between Edc Exposure (Low/high) and Eeqmentioning
confidence: 99%
“…Indeed, some studies have shown that the presence of EDCs in anthropized watercourses, due to inadequate urban wastewater management, can lead to pollution of drinking water sources. Since drinking water treatment technology can be ineffective in removing these compounds, consumption of tap water can cause the consequent EDC intake [18,20,70]. Exposure in urban areas may also occur through inhalation of atmospheric EDCs released by human activities (e.g., traffic, industrial processes, waste incineration) [21,71].…”
Section: Relationship Between Edc Exposure (Low/high) and Eeqmentioning
confidence: 99%
“…Consequently, additional experiments should be performed to establish the possible environmental and human risk of these DPs. The biodegradability tests of the treated solutions it's a well indicator of the possible generation of bioaccumulative DPS that could be even more toxic than the initial molecule (Jojoa-Sierra et al 2017; Rosseti 2017; Maurício et al 2018). Therefore, a modi ed Zahn Wellens test was carried out to evaluate biodegradability to the treated solutions at different times along the PEF process (0, 45 and 90 min of treatment).…”
Section: Biodegradability Test Of Smx and Tmp Solutions Submitted The Pef Systemmentioning
confidence: 99%
“…Emerging pollutants (or Contaminants of Emerging Concern -CECs) are compounds which are detected at low levels in surface water and are not commonly monitored/regulated but may have an impact on aquatic life and ecosystem and on human health. 1,2 The group of CECs consists mainly of antibiotics, 3 pharmaceutics, 4 steroids, 5 endocrine disruptors, 6 hormones, 7 industrial additives, 8 chemicals from personal care products, 9 other chemicals, 10 and also microbeads and microplastics. 11,12 One of the main concerns are antibiotics and pharmaceutics in general, because they can accumulate in aquatic organisms and consequently in humans with unknown health effects.…”
Section: Introductionmentioning
confidence: 99%